A simplified model for solving wheel-rail non-Hertzian normal contact problem under the influence of yaw angle. (15th May 2020) - Sun, Yu; Zhai, Wanming; Ye, Yunguang; Zhu, Liming; Guo, Yu
Highlights: l The approximate expression of the wheel-rail non-Hertzian contact problem considering the yaw angle is proposed. l A simplified wheel-rail non-Hertzian model (MKP-YAW model) that can consider the effect of yaw angle is built. l The MKP-YAW model has a relative good computational accuracy. Abstract: Wheelset yaw motion significantly affects wheel-rail non-Hertzian contact behaviour, but currently, few wheel-rail normal contact models consider this issue. In this paper, a simplified wheel-rail contact model is built to study the wheel-rail non-Hertzian normal contact problem considering the yaw angle. First, three basic assumptions for the approximate calculation of this problem are proposed and are validated by using results calculated by Kalker's variational method (KVM), and the approximate expression of the wheel-rail non-Hertzian contact problem considering the yaw angle is obtained based on these assumptions. Then, the approximate expression is applied to the MKP (Modified Kik–Piotrowski) contact model, and an improved MKP model that considers the wheelset yaw angle is proposed, i.e., the MKP-YAW model. Compared with the results calculated by KVM, the computational accuracy of the proposed MKP-YAW model in calculating the wheel-rail contact considering the yaw angle is similar to that of the MKP contact model in calculating the wheel-rail contact without considering the yaw angle. Graphical abstract: Image, graphical abstract